2007 46th IEEE Conference on Decision and Control 2007
DOI: 10.1109/cdc.2007.4434433
|View full text |Cite
|
Sign up to set email alerts
|

Limit cycles analysis in hybrid anti-lock braking systems

Abstract: We investigate the stability and robustness properties of Anti-lock Braking Systems based on actuators with on/off dynamics. Namely, we propose a hybrid ABS controller which gives rise to an asymptotically stable limit cycle on the wheel slip. The proposed approach allows to derive exact information on the maximum allowable uncertainty in the measured variables which guarantee the cycle stability. Moreover, a structural stability analysis is performed with respect to different road conditions and to the actuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Development of anti-lock control systems has attracted considerable attention of many researchers. Wheel slip controllers (Petersen, Johansen, Kalkkuhl, & Lüdemann, 2001;Vries, Fehn, & Rixen, 2010) and anti-lock strategies based on logic switching (Tanelli, Osorio, di Bernardo, Savaresi, & Astolfi, 2007;PasillasLépine, 2006) are the most widely used control methods in the anti-lock brake systems.…”
Section: Anti-lock Brake Systemsmentioning
confidence: 99%
“…Development of anti-lock control systems has attracted considerable attention of many researchers. Wheel slip controllers (Petersen, Johansen, Kalkkuhl, & Lüdemann, 2001;Vries, Fehn, & Rixen, 2010) and anti-lock strategies based on logic switching (Tanelli, Osorio, di Bernardo, Savaresi, & Astolfi, 2007;PasillasLépine, 2006) are the most widely used control methods in the anti-lock brake systems.…”
Section: Anti-lock Brake Systemsmentioning
confidence: 99%
“…ABS controllers are indeed a safety critical application, as they have to take care of managing panic-brakes which cannot be handled by common drivers. The design of an appropriate controller for these systems has been presented in [12], where it has been shown that the closed loop system has the desired stability properties. System and Actuator Model.…”
Section: A Application Descriptionmentioning
confidence: 99%
“…System and Actuator Model. The braking dynamics have been modeled based on a quarter car model, [12]. The considered actuator is an HAB, which, according to its physical characteristics, is only capable of providing three control actions: Increase the brake pressure; Hold the brake pressure and Decrease the brake pressure.…”
Section: A Application Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABS systems have been commercially available on cars for more than 20 years [1]. In the past few years, with the introduction of the electronic stability control (ESC), electro-mechanical (EM) brakes and drive-by-wire systems, the literature on wheel-slip control for cars has seen many important contributions [2][3][4][5][6][7][8]. Notably, the goal has cannot guarantee satisfying performance; instead, linear-parameter-varying (LPV) techniques can be successfully used to automatically schedule the controller with respect to different operating conditions, in order to design a feedback control law.…”
Section: Introductionmentioning
confidence: 99%